Increasing Peak Expiratory Flow Rate Through a Combination of the Tripod Position and Balloon-Blowing Exercise in PMR Members - Enny Virda; Refin Amanda Putri Nabila; Syeira Trina Zarina; Muchamad Yafi’ Aditiya Fawwaz (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Peak Expiratory Flow (PEF) is a lung function indicator that reflects the ability to exhale air to the maximum extent. The combination of the tripod position and balloon-blowing exercise is believed to improve lung ventilation and PEFR values. This study aimed to improve peak expiratory flow rate through a combination of the tripod position and balloon-blowing exercise among PMR members at SMAN 1 Bangsal. This study employed a pre-experimental design using a one-group pretest-posttest approach with a sample of 33 PMR members selected using total sampling. Data were collected using standard operating procedures (SOPs) and observation sheets. The results were analyzed using the Wilcoxon rank-sum test, yielding a p-value of 0.000 with α < 0.05, indicating a significant effect of the combination of the tripod position and balloon-blowing exercise on peak expiratory flow among PMR members at SMAN 1 Bangsal. The importance of implementing the combination of the tripod position and balloon-blowing exercise as a nonpharmacological intervention can help improve peak expiratory flow, as both interventions are capable of optimizing pulmonary ventilation, strengthen the respiratory muscles and maximize exhalation capacity.